An experimental study on the formation of methoxyaromatics during pyrolysis of Eucalyptus pulverulenta: Yields and mechanisms. (October 2016) - Xu, Jing; Tahmasebi, Arash; Yu, Jianglong
Highlights: The yield of bio-oil was higher when Na2 CO3 was used as catalyst. Na2 CO3 and NaOH promoted the formation of methoxyaromatics and phenolics. Methoxyaromatics reached a maximum of 63.4%(area) at 400 °C in presence of Na2 CO3 . Abstracts: The production of bio-oil rich in methoxyaromatics during catalytic pyrolysis of Eucalyptus pulverulenta (EP) was studied using a fixed-bed reactor in the temperature range of 300–500 °C and the bio-oil composition was analyzed by using a GC–MS. The results showed that the highest bio-oil yield of 38.45 wt% was obtained at 400 °C in the presence of Na2 CO3, and the concentration of methoxyaromatics reached the maximum value of 63.4%(area) in the bio-oil. The major methoxyaromatics identified in bio-oil were guaiacol, syringol, 4-ethyl-2-methoxy phenol, and 1, 2, 4-trimethoxybenzene. The analysis of gaseous products indicated that CO2 was the major gas at low-temperatures and concentrations of H2 and CH4 increased with increasing pyrolysis temperature. Na2 CO3 promoted the formation of methoxyaromatics, while NaOH seems to have enhanced the formation of phenolics. The mechanism of the formation of methoxyaromatics during pyrolysis of EP was proposed.